2022
DOI: 10.1302/2633-1462.310.bjo-2022-0114.r1
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year outcome following surgical treatment of femoroacetabular impingement

Abstract: Aims The primary aim of this study was to determine the ten-year outcome following surgical treatment for femoroacetabular impingement (FAI). We assessed whether the evolution of practice from open to arthroscopic techniques influenced outcomes and tested whether any patient, radiological, or surgical factors were associated with outcome. Methods Prospectively collected data of a consecutive single-surgeon cohort, operated for FAI between January 2005 and January 2015, were retrospectively studied. The cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…As techniques in hip arthroscopic surgery continue to evolve, it is important to evaluate whether such changes translate to improved outcomes. Grammatopoulos et al 25 reported 10-year outcomes including patients who underwent open treatment with surgical hip dislocation, combined open and arthroscopic treatment, arthroscopic labral debridement, and arthroscopic labral repair and did not find, in their case series, clear relationships between the technique and outcomes. However, it is known now that correction of bony morphology is critical, labral debridement is inferior to repair, and capsular closure is paramount to better clinical outcomes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As techniques in hip arthroscopic surgery continue to evolve, it is important to evaluate whether such changes translate to improved outcomes. Grammatopoulos et al 25 reported 10-year outcomes including patients who underwent open treatment with surgical hip dislocation, combined open and arthroscopic treatment, arthroscopic labral debridement, and arthroscopic labral repair and did not find, in their case series, clear relationships between the technique and outcomes. However, it is known now that correction of bony morphology is critical, labral debridement is inferior to repair, and capsular closure is paramount to better clinical outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Although there are valuable longer-term studies on hip arthroscopic surgery in the literature, many that are currently available report on cases in which contemporary techniques were not employed. For example, previous long-term follow-up studies have described surgical techniques that approach the central compartment only, 8 perform debridement or resection of the labrum as opposed to repair as a major treatment method, 7,19,25,40,72 utilize open techniques, 25 and do not include or specify capsular closure/repair. 10,49,71,72 Moreover, many of these studies are limited by a low rate (<50%) of follow-up, which may bias results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has numerous strengths. First, although long-term studies on hip arthroscopy for FAIS currently exist in the literature, many report on cases in which contemporary hip arthroscopy techniques were not used, and older techniques such as open techniques, 22 the majority of labral treatment was debridement, 6,20,22,38,64 and no capsular management were performed. 9,44,63,64 To our knowledge, this is the first 10-year investigation that uses contemporary approaches (ie, labral repair, capsular closure, femoral osteochondroplasty) specifically comparing patients with To ¨nnis grade 0 versus grade 1.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions for treating FAI are focused on labrum repair and osteochondroplasty to remove the impingement and alleviate symptoms. Femoroacetabular impingement surgery is reported to provide lasting improvements in function and a joint preservation rate of 90.4% at 10 years [14]. Nevertheless, some patients progress to hip OA after surgery.…”
Section: Introductionmentioning
confidence: 99%